Kerala's Case for the Third Five Year Plan - Government of Kerala (Government of Kerala, 1962)
Kerala’s case for the Third Five-Year Plan emphasizes the critical need for structured, state-specific development strategies to address pressing socio-economic challenges. The plan aims to achieve a national income growth of over 5% per annum while ensuring food self-sufficiency and enhancing agricultural production. Industrial expansion is prioritized through the development of basic industries, including steel, fuel, and power, alongside capabilities for machine manufacturing, to diversify the economy and create sustainable employment. With over 1,000 people per square mile and a 2.3% annual population growth, Kerala faces acute pressures on land resources, resulting in chronic food deficits and significant seasonal unemployment, including among educated youth. The Third Plan proposes an ambitious total outlay of Rs. 11,250 crores, including Rs. 7,250 crores for public sector investment, targeting agriculture, irrigation, power, and social services. The plan underscores the need for equitable regional investment, particularly in light of Kerala’s underperformance under the Second Plan, where central assistance and private sector contributions fell short of requirements. By addressing population pressures, economic disparities, and infrastructural deficiencies, the Third Five-Year Plan advocates a holistic approach to economic self-sufficiency and balanced growth. The memorandum calls for urgent action from the Planning Commission and central government to ensure Kerala’s development goals are met, promoting social stability, regional equity, and long-term economic sustainability.
Government of Kerala, Planning & Development Department
Government of Kerala, Planning & Development Department
Keywords: Kerala Third Five-Year Plan; Socio-Economic Development; National Income Growth; Food Self-Sufficiency; Industrial Expansion; Employment Generation; Wealth Distribution; Population Density Challenges; Agricultural Economy; Food Deficit; Public Sector Investment; Regional Equity